2019
DOI: 10.1111/jmp.12405
|View full text |Cite
|
Sign up to set email alerts
|

Complete rectal prolapse in wild anubis baboons (Papio anubis)

Abstract: Rectal prolapse is classified as either incomplete, which involves only the rectal mucosa, or complete, in which the full thickness of the rectum prolapses through the anus. 1 Rectal prolapse can result from various factors, including straining related to cystitis, chronic coughing, parasites and defecation disorders due to environmental or social distress. 1,2 Rectal prolapse has been observed more often in captive primates 3-7 than in wild primates. Four wild chacma baboons (P. ursinus) that had fed extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One of the first baboons we trapped developed a prolapsed rectum, which we believe resulted from a combination of heavy consumption of maize and distress as the baboon evaded us in the cage trap during our initial attempts to sedate her with a syringe (Taniguchi, Isbell, Bidner, & Matsumoto‐Oda, ). When we switched to a blowpipe, she was immobilized quickly, and we were then able to reposition her rectum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first baboons we trapped developed a prolapsed rectum, which we believe resulted from a combination of heavy consumption of maize and distress as the baboon evaded us in the cage trap during our initial attempts to sedate her with a syringe (Taniguchi, Isbell, Bidner, & Matsumoto‐Oda, ). When we switched to a blowpipe, she was immobilized quickly, and we were then able to reposition her rectum.…”
Section: Resultsmentioning
confidence: 99%
“…In a different study at our field site, another female baboon was observed with a prolapsed rectum after feeding heavily on maize used as bait for trapping, but she was not trapped. A highly limited diet with foods low in water content and high in fiber, as is found in maize, can cause rectal prolapses (Taniguchi et al, ). Unexpected situations also arose that required us to make quick decisions or judgment calls.…”
Section: Discussionmentioning
confidence: 99%